Epidural administration of ropivacaine and midazolam is superior to intra-articular administration as postoperative analgesia after isolated arthroscopic anterior cruciate ligament reconstruction with hamstrings autograft: a randomized controlled clinical trial - Aldape Rivas, Dareny Esmeralda; Padilla Medina, José Ramón; Espinosa Galindo, Ana María; De la Garza Castro, Santiago; Palacios Ríos, Dionicio; Peña Martínez, Víctor Manuel; Morales Avalos, Rodolfo (Elsevier, 2024)
Objective: Reconstructive surgery of the anterior cruciate ligament (ACL) is quite common, previous studies have documented that adequate pain control in the early phases of the postoperative period translates into early mobility and a rapid start of rehabilitation. Therefore, the search for new strategies for postoperative pain control is justified. The aim of this study was to compare intra-articular to the epidural administration of ropivacaine and midazolam as postoperative analgesia after arthroscopic ACL reconstruction with hamstring autograft (HA). Material and methods: Double-blinded, prospective randomized clinical trial included 108 consecutive patients aged from 18 to 50 years that had undergone arthroscopic ACL reconstruction with HA. The patients were randomly assigned to 2 groups. The first group received intraarticular ropivacaine and midazolam. The second group received epidural ropivacaine and midazolam. The need for rescue analgesia, the postoperative pain experienced, side effects and complications of the analgesic drugs were evaluated. Results: The intra-articular group received statistically significantly higher mean doses of rescue analgesia on the first two days (2.8 1.0 vs. 1.3 0.6 in the epidural group; p ¼ 0.001). Visual Analogue Scale scores at flexion were statistically significantly higher in the intra-articular group over the entire study period. The intra-articular group also reported a statistically significantly lower range-of-motion 87 15 vs. 102 11 in the epidural group (p ¼ 0.001). Conclusions: Epidural administration of ropivacaine combined with midazolam in patients undergoing primary ACL reconstruction with HA was clinically and significantly better relative to rescue analgesia and the intensity of pain in the first 48 postoperative hours when compared to intraarticular administration. There was no difference in terms of adverse effects and complications.